Adding the third dimension to studies of parallel evolution of morphology and function: An exploration based on parapatric lake‐stream stickleback. Issue 23 (17th November 2020) - Haines, Grant E.; Stuart, Yoel E.; Hanson, Dieta; Tasneem, Tania; Bolnick, Daniel I.; Larsson, Hans C. E.; Hendry, Andrew P.
Abstract: Recent methodological advances have led to a rapid expansion of evolutionary studies employing three‐dimensional landmark‐based geometric morphometrics (GM). GM methods generally enable researchers to capture and compare complex shape phenotypes, and to quantify their relationship to environmental gradients. However, some recent studies have shown that the common, inexpensive, and relatively rapid two‐dimensional GM methods can distort important information and produce misleading results because they cannot capture variation in the depth ( Z ) dimension. We use micro‐CT scanned threespine stickleback ( Gasterosteus aculeatus Linnaeus, 1758) from six parapatric lake‐stream populations on Vancouver Island, British Columbia, to test whether the loss of the depth dimension in 2D GM studies results in misleading interpretations of parallel evolution. Using joint locations described with 2D or 3D landmarks, we compare results from separate 2D and 3D shape spaces, from a combined 2D‐3D shape space, and from estimates of biomechanical function. We show that, although shape is distorted enough in 2D projections to strongly influence the interpretation of morphological parallelism, estimates of biomechanical function are relatively robust to the loss of the Z dimension. Abstract : The use of methods to acquire 3D morphological data is becoming increasingly widespread, but remains expensive and time consuming. We investigated whether 2D morphometric landmark data, which can be acquired much more quickly and with less expensive equipment, distorts interpretation of parallel evolution in threespine stickleback. Separately, we test whether morphological parallelism is distorted by 2D data, and whether calculations of biomechanical function derived from 2D data are affected by the loss of the width dimension.